Managing Disorientation of Time and Place in Dementia Patients Using Bluetooth Sensors: Identification of Failure Modes on ESC through RCM - Iqbal, Sarwat; Ahsan, Kamran; Hussain, Muhammad Azhar; Nadeem, Adnan; Saeed, Muhammad; Ahmed, Sohaib (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Assistive technology has the potential to support persons with dementia (PWDs) in their daily life activities and provide them quality of life services. This paper proposes a novel mechanism in order to manage disorientation or time and place problem of PWD through the use of Bluetooth low energy devices, smart watch and smart phone/ tablet. The proposed mechanism was verified in a real environment having the facilities an ordinary PWD avail in his home environment and also in lab environment. All of the participants were volunteers from research group personal contacts. Volunteers spend time in the environment and results were generated. Experimental result showed that the proposed mechanism provided an accurate real time ubiquitous monitoring of PWD. Successful detection of PWD presence in real time and notification to caregiver observed in all cases.